Motivation and Challenges Faced by Distance Education Learners: Insights from Bicol University Open University, Philippines - Benedicto Balilo; Martha Joy RUIVIVAR; Jose Carlo B. LAVAPIE (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
The increasing reliance on distance education (DE) requires a comprehensive understanding of student motivations and the multifaceted challenges they encounter in asynchronous learning environments. This study aims to explore the perceptions, motivations, and obstacles faced by 67 learners enrolled in Bicol University Open University (BUOU) programs during the first semester of the 2023–2024 academic year. Utilizing a descriptive research approach, the study identified that students were primarily motivated by convenience, flexibility in time management, and the ability to balance professional work with family responsibilities. However, significant challenges were identified, led by technical and connectivity issues (21.3%), time management difficulties (19.1%), a lack of face-to-face interaction (14.9%), and miscommunication (12.8%), followed by limited resource access (11.7%), self-discipline issues (11.7%), and insufficient technological proficiency (7.4%). Despite these hurdles, learners successfully navigated their programs through rigorous self-discipline and consistent support from the faculty-in-charge (FIC). The study concludes that while DE offers essential flexibility, its long-term success depends on addressing technical and interactive gaps. It is recommended that the institution establish a dedicated learning hub with stable connectivity, increase student engagement through diverse online activities, and strengthen synchronous sessions by incorporating high-impact topics such as emerging technological trends and international research publication strategies.